Can emergency nurses safely and effectively insert fascia iliaca blocks in patients with a fractured neck of femur? A prospective cohort study in an Australian emergency department. Issue 23 (9th June 2021) - Gawthorne, Julie; Stevens, Jennifer; Faux, Steven G.; Leung, Julie; McInnes, Elizabeth; Fasugba, Oyebola; Mcelduff, Benjamin; Middleton, Sandy
Abstract : Aims and objectives: To compare the effectiveness and safety of ultrasound‐guided fascia iliaca block (FIB) insertion in patients with fractured neck of femur by trained emergency nurses with insertion by doctors. Background: The FIB is an effective and safe form of analgesia for patients with hip fracture presenting to the emergency department (ED). While it has traditionally been inserted by medical doctors, no evidence exists comparing the effectiveness and safety of FIB insertion by nurses compared with doctors. Design: A prospective cohort study. Methods: The study was conducted in an Australian metropolitan ED. Patients admitted to the ED with suspected or confirmed fractured neck of femur had a FIB inserted under ultrasound guidance by either a trained emergency nurse or doctor. A retrospective medical record audit was undertaken of consecutive ED patients presenting between January 2013–December 2017. Reporting of this study followed the Strengthening the Reporting of Observational Studies in Epidemiology guidelines for cohort studies. Results: Of the 472 patients eligible for a FIB, 322 (68%) had one inserted. A majority were inserted by doctors ( n = 207, 64.3%) with 22.4% ( n = 72) by nurses and in 13.3% ( n = 43) of patients the clinician was not documented. There were no differences between the nurse‐inserted and doctor‐inserted groups for mean pain scores 1 hr post‐FIB insertion; clinically significant reduction (≥30%) in pain score 1 hr post‐FIB insertion; pain score 4 hr post‐FIB insertion; delirium incidence; opioid use post‐FIB insertion; or time to FIB insertion. No adverse events were identified in either group. Conclusion: Insertion of FIBs by trained emergency nurses is as effective and safe as insertion by doctors in patients with fractured neck of femur in the ED. Senior emergency nurses should routinely be inserting FIB as a form of analgesia for patients with hip fracture. Relevance to clinical practice: Our study showed trained emergency nurses can safely and effectively insert fascia iliaca blocks in patients with hip fractures. Pain was significantly reduced in a majority of patients with no reported complications. Emergency nurses should be trained to insert fascia iliaca blocks in patients with hip fractures.